2014
DOI: 10.1105/tpc.114.124743
|View full text |Cite
|
Sign up to set email alerts
|

An EAR-Dependent Regulatory Module Promotes Male Germ Cell Division and Sperm Fertility in Arabidopsis

Abstract: The production of the sperm cells in angiosperms requires coordination of cell division and cell differentiation. In Arabidopsis thaliana, the germline-specific MYB protein DUO1 integrates these processes, but the regulatory hierarchy in which DUO1 functions is unknown. Here, we identify an essential role for two germline-specific DUO1 target genes, DAZ1 and DAZ2, which encode EAR motif-containing C 2 H 2 -type zinc finger proteins. We show that DAZ1/DAZ2 are required for germ cell division and for the proper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 63 publications
1
83
0
Order By: Relevance
“…Analysis of the microscopic images in comparison with previously published TEM images of intact sperm cells within A. thaliana pollen (Owen and Makaroff 1995;Borg et al 2014) revealed that all of the sorted sperms inspected (n = 413) completely lacked the plasma membrane (Fig. 3d).…”
Section: Purified Sperm Populations Are Sperm Nucleimentioning
confidence: 80%
See 1 more Smart Citation
“…Analysis of the microscopic images in comparison with previously published TEM images of intact sperm cells within A. thaliana pollen (Owen and Makaroff 1995;Borg et al 2014) revealed that all of the sorted sperms inspected (n = 413) completely lacked the plasma membrane (Fig. 3d).…”
Section: Purified Sperm Populations Are Sperm Nucleimentioning
confidence: 80%
“…Apparently, not only vegetative cell nuclei but also duo1 mutant sperm-like cell nuclei are more fragile than wild-type sperm nuclei during sorting. It is known that mutant cells without the DUO1 pathways fail to differentiate (Borg et al 2014), which is caused by alterations in gene expression. As DUO1 target genes include genes coding for proteins that are localized to the plasma membrane and genes involved in chromatin structure (Borg et al 2011), it is reasonable to assume that duo1 mutant spermlike cells could behave differently from wild-type sperm cells during purification steps.…”
Section: Dna Content Is a Determinant For Sybr Green-activated Nucleumentioning
confidence: 99%
“…3). One major regulator of sperm cell identity and cell cycle progression is the transcription factor DUO POLLEN1 (DUO1; Rotman et al, 2005;Borg et al, 2011Borg et al, , 2014. In the loss-of-function mutant duo1, the generative cell fails to divide to generate two sperm cells, and the mutant pollen cannot fertilize the female egg cell or central cell.…”
Section: Discussionmentioning
confidence: 99%
“…Although a putative GRSF binding site was predicted in the promoter region of DUO1 (Haerizadeh et al, 2006), a truncated version of DUO1 promoter excluding the putative GRSF binding site did not prevent germline-specific expression, nor did it result in constitutive expression (Brownfield et al, 2009a). On the other hand, MYB binding sites were overrepresented in the promoters of DUO1-activated target (DAT) genes (Borg et al, 2011(Borg et al, , 2014. DUO1 directly regulates the expression of DATs through binding to the MYB sites in the promoter regions.…”
Section: Gene Expression In Male Germline Cells Is Regulated By Divermentioning
confidence: 99%
“…Presence of GRSF binding sequences in other male gamete-expressed genes suggested widespread control of male gamete gene expression by this functionally conserved sequence (Haerizadeh et al, 2006). DUO1 functions in another way, by directly binding to MYB sites to activate its target genes DUO1-ACTIVATED ZINC FINGER1 (DAZ1) and DAZ2, which encode transacting transcriptional repressors (Rotman et al, 2005;Brownfield et al, 2009a;Borg et al, 2011Borg et al, , 2014. A putative GRSF binding site was predicted in the DUO1 promoter (Haerizadeh et al, 2006).…”
mentioning
confidence: 99%